Preventing and countering violent extremism : designing and evaluating evidence-based programs - Williams, Michael J. (Political violence, 2021)
This textbook serves as a guide to design and evaluate evidence-based programs intended to prevent or counter violent extremism (P/CVE). Violent extremism and related hate crimes are problems which confront societies in virtually every region of the world; this text examines how we can prevent or counter violent extremism using a systematic, evidence-based approach. The book, equal parts theoretical, methodological and applied, represents the first science-based guide for understanding "what makes hate," and how to design and evaluate programs intended to prevent this. Though designed to serve as a primary course textbook, the work can readily serve as a how-to guide for self-study, given its abundant links to freely available online toolkits and templates. As such, it is designed to inform both students and practitioners alike with respect to the management, design, or evaluation of programs intended to prevent or counter violent extremism. Written by a leading social scientist in the field of P/CVE program evaluation, this book is rich in both scientific rigor and examples from the "real world" of research and evaluation dedicated to P/CVE.